Legacy, ghosts, chronoference: the re-presentation of the past in Katja Petrowskaja’s “Das Foto schaute mich an” (2022) - Vedder, Ulrike (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2026)
Katja Petrowskaja’s collection of short texts on selected photographs was published as a book in 2022; previously, these texts appeared as columns in the Frankfurter Allgemeine Sonntagszeitung every three weeks for several years. Photographs already played a certain role in her first novel Vielleicht Esther (2014). Das Foto schaute mich an is also about the searching reflection of a connection between the present and the past on the basis of photographs, about the concentrated questioning of visual details in an attempt to make them speak – all against the horizon of the possibilities and aporias of historical memory in the context of the violent history of the 20th century. Based on some of the columns, the essay analyses the intricate temporal relationships that relate to the question of making the past present and that come about in the interplay between literature and photography. The three perspectives ‘legacy and heritage’, ‘ghosts and afterlife’ and ‘chronoference’ play a decisive role here.
Keywords: photography; memory; intermediality; representation of time; contemporary literature